Np(V) solubility, speciation and solid phase formation in alkaline CaCl2 solutions. Part I: experimental results - Fellhauer, David; Rothe, Jörg; Altmaier, Marcus; Neck, Volker; Runke, Jörg; Wiss, Thierry; Fanghänel, Thomas (Radiochimica acta, 2016)
Abstract The aqueous chemistry of Np(V) in alkaline 0.01 to 5.5 M CaCl2 solutions at T = 23 ± 2 ℃ was thoroughly studied by long-term batch solubility experiments from both over- and undersaturation. Applying a comprehensive set of experimental and spectroscopic techniques including Vis/NIR and Np L3-edge EXAFS, the solubility controlling Np(V) solid phases and the predominant aqueous Np(V) species were identified. The results demonstrate that the solubility behavior of Np(V) in alkaline CaCl2 solutions differs completely from the one reported for alkaline NaCl and NaClO4 solutions: as solubility limiting solid phases, three so far not considered Ca-Np(V)-OH compounds were identified and their solubility and stability in CaCl2 solutions analyzed: CaNpO2(OH)2.6Cl0.4 · 2H2O(s) (I) (metastable), Ca0.5NpO2(OH)2 · 1.3H2O(s) (II) (long-term metastable) and Ca0.5NpO2(OH)2(s) (III) (stable). The considerably higher stability of these (qua)ternary phases which readily form in alkaline CaCl2 solutions from oversaturation (addition of NpO2+) and undersaturation (addition of binary NpO2OH(am)) limit the Np(V) equilibrium concentrations to values that are up to 3 log-units lower compared to those for NpO2OH(am) in NaCl and NaClO4 systems. Based on systematic evaluation of the pH dependence (solubility curve slopes), Vis/NIR and EXAFS spectroscopic information, unhydrolysed NpO2+ and innersphere chloro complexes, NpO2Cl(aq) and Caz[NpO2Cl]2z+ with z = 1 (EXAFS, Vis/NIR), were identified as prevailing Np(V) species in less alkaline solutions with pHm < 10.5 for [CaCl2] ≤ 2.0 M and [CaCl2] > 2.0 M, respectively. The steep increase of the Np(V) solubility for pHm > 11 with slopes of approximately + 2.5 (for solid phase (I)) and + 3 (for solids (II) and (III)) as well as the Np L3-edge EXAFS results for the aqueous Np(V) species in 4.5 M CaCl2/pHm ≈ 12 confirm the presence of ternary Ca-Np(V)-OH complexes Cax[NpO2(OH)2]2x-1 (x ≈ 1 is estimated within the thermodynamic evaluation in a subsequent paper (Fellhauer, D., Altmaier, M., Gaona, X., Lützenkirchen, J., Fanghänel, Th., Np(V) solubility, speciation and solid phase formation in alkaline CaCl2 solutions. Part II: Thermodynamics and implications for source term estimations of nuclear waste disposal (Radiochim. Acta, DOI 10.1515/ract-2015-2490), in the following referred to as “Part II” [1]) and Cay[NpO2(OH)5]2y-4 with y ≈ 2.4 ± 1.5 (EXAFS result) as predominant Np(V) hydrolysis species in solution for [CaCl2] ≥ 0.25 and pHm > 10.5. The thermodynamic evaluation and implications of the new findings with respect to source term estimations for nuclear waste disposal scenarios are discussed in “Part II” [1]).
Gesehen am 15.05.2020